Hollow Fibre-Supported Liquid Membrane for the Determination of Sulfonamide Residues in Egg Samples - Eskinder Teklu Bekele; S. Dube; M. M. Nindi (Journal of Chemistry)
In this study, a three-phase hollow fibre-supported liquid membrane (HF-SLM) technique incorporated with high-performance liquid chromatography (HPLC) coupled with diode array detection (DAD) was developed for the extraction, clean-up, and determination of fifteen sulfonamide residues in chicken egg samples. The residues were extracted from the 5 mL sample solution of pH 2.5 into a thin layer of organic phase (1-octanol with 10% TOPO) immobilised in hollow fibre pores and then back-extracted into approximately 6 μL of aqueous phase (pH 13) located in the lumen of the hollow fibre. After extraction, 6 μL of the acceptor phase was injected into an HPLC instrument for subsequent analysis. Under optimum conditions, the limit of detection (LOD) and limit of quantification (LOQ) values ranged from 0.8–7.9 μg·kg−1 and from 2.4–21.0 μg·kg−1, respectively, linearity in the range of 5 1 000 μg·kg−1, and intra- and inter-day precision (%RSD) values at three concentration levels (50, 100, and 500 μg·L−1) ranged from 6.2–15.7%, 7.3–15.0%, and 7.3–14.6%; and 6.4–17.4%, 4.3–16.2%, and 8.3–16.5%, respectively, were obtained. The accuracy of the method, expressed as percentage recovery, was in the range of 71.0–98.7%, with corresponding %RSD (n = 6) values ranging from 1.9–9.9% being obtained. The developed method provided enrichment factors in the range of 17.1 to 541.4. The applicability of the proposed method was also evaluated by analysing egg samples, which were randomly collected from local supermarkets located in Gauteng Province, South Africa. The results obtained revealed that the developed method has the potential to be used as an alternative method for the determination of sulfonamide residues in egg and related complex samples.